Camphor-Based CVD Bilayer Graphene/Si Heterostructures for Self-Powered and Broadband Photodetection - Dung-Sheng Tsai; Ping-Yu Chiang; Meng-Lin Tsai; Wei-Chen Tu; Chi Chen; Shih-Lun Chen; Ching-Hsueh Chiu; Chen-Yu Li; Wu-Yih Uen (Micromachines, 2020)
This work demonstrates a self-powered and broadband photodetector using a heterojunction formed by camphor-based chemical vaper deposition (CVD) bilayer graphene on p-Si substrates. Here, graphene/p-Si heterostructures and graphene layers serve as ultra-shallow junctions for UV absorption and zero bandgap junction materials (<Si bandgap (1.1 eV)) for long-wave near-infrared (LWNIR) absorption, respectively. According to the Raman spectra and large-area (16 × 16 μm2) Raman mapping, a low-defect, >95% coverage bilayer and high-uniformity graphene were successfully obtained by camphor-based CVD processes. Furthermore, the carrier mobility of the camphor-based CVD bilayer graphene at room temperature is 1.8 × 103 cm2/V·s. Due to the incorporation of camphor-based CVD graphene, the graphene/p-Si Schottky junctions show a good rectification property (rectification ratio of ~110 at ± 2 V) and good performance as a self-powered (under zero bias) photodetector from UV to LWNIR. The photocurrent to dark current ratio (PDCR) value is up to 230 at 0 V under white light illumination, and the detectivity (D*) is 8 × 1012 cmHz1/2/W at 560 nm. Furthermore, the photodetector (PD) response/decay time (i.e., rise/fall time) is ~118/120 μs. These results support the camphor-based CVD bilayer graphene/Si Schottky PDs for use in self-powered and ultra-broadband light detection in the future.